The cinesthetic montage of music-video: hearing the image and seeing the sound - Strand, Joachim (Curtin University, 2006)
This thesis examines the interconnected relationship that exists between sound and moving-image in the music-video. The flow of images used in many music videos often carries no definite meaning. Rather, the viewer must perceive the physiological sensations of the video's audiovisual expression to make sense of it. Thus, both the expression and the perception of music-video is a cross-modal process. Using Vivian Sobchack's theory of cinesthetics as a framework, the thesis contends that the music-video produces an aural visuality in which sound can be cinesthetically expressed and perceived as image and the image perceived and expressed as sound.